Effects of virtual reality therapy on upper limb function after stroke and the role of neuroimaging as a predictor of a better response - Goncalves, Maicon Gabriel [UNESP] (2018)
Background: Virtual reality therapy (VRT) is an interactive intervention that induces neuroplasticity. The aim was to evaluate the effects of VRT associated with conventional rehabilitation for an upper limb after stroke, and the neuroimaging predictors of a better response to VRT. Methods: Patients with stroke were selected, and clinical neurological, upper limb function, and quality of life were evaluated. Statistical analysis was performed using a linear model comparing pre- and post-VRT. Lesions were segmented in the post-stroke computed tomography. A voxel-based lesion-symptom mapping approach was used to investigate the relationship between the lesion and upper limb function. Results: Eighteen patients were studied (55.5 +/- 13.9 years of age). Quality of life, functional independence, and dexterity of the upper limb showed improvement after VRT (p < 0.001). Neuroimaging analysis showed negative correlations between the internal capsule lesion and functional recovery. Conclusion: VRT showed benefits for patients with stroke, but when there was an internal capsule lesion, a worse response was observed.